2019
DOI: 10.1007/s40629-019-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Update of reference values for IgG antibodies against typical antigens of hypersensitivity pneumonitis

Abstract: Background Specific (s)IgG antibodies against environmental and occupational antigens, especially from bacteria, moulds, yeasts, birds and chemicals play an important role for hypersensitivity pneumonitis (HP). An increased serum level of sIgG is one criterion in the diagnostic procedure of HP and crucial for the detection of the triggering antigen for successful avoidance of further exposure. In contrast to specific IgE, sIgG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…The clinically relevant concentration for detecting antibodies varies depending on the application. For the detection of antibodies used for the diagnosis of infectious diseases (Fiorentini et al, 2008;Rostenberg and Peñ aloza, 1978;Barletta et al, 2004;Raulf et al, 2019), the concentration level expected to have in clinical samples (i.e. blood, serum) is -depending on the stage of infection -in the pM to low nM range.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically relevant concentration for detecting antibodies varies depending on the application. For the detection of antibodies used for the diagnosis of infectious diseases (Fiorentini et al, 2008;Rostenberg and Peñ aloza, 1978;Barletta et al, 2004;Raulf et al, 2019), the concentration level expected to have in clinical samples (i.e. blood, serum) is -depending on the stage of infection -in the pM to low nM range.…”
Section: Discussionmentioning
confidence: 99%
“…For simple aspergilloma in pulmonary tuberculosis patients, the same working group found a sensitivity of 63.5% and a specificity of 98.3% using a cut-off of 27.3 mg/L. However, the Gm3 cut-off-level is still under discussion, as a recent multicentric study found a median Gm3 of 21.3 mg/L and a 90% quantile for Gm3 of 78 mg/L in a population of 121 healthy donors (Raulf et al, 2019). The working group suggested that IgG values higher than at least 90% of the healthy donor group indicate elevated levels, which is more consistent with our findings of a cut-off-level of 78.05 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the presence of cross-reactive antigenic reactions between different bird species or different avian matrices, especially for pigeons 14,[27][28][29] . Recently, significant correlations have been found in serological analyses between pigeon, duck, and goose antigens 11 . Based on the BLASTp alignment, our results showed that the amino-acid sequence of duck IGLL has higher identity with goose IGLL (ID: 81%) than pigeon IGLL1 (ID: 65%) (Supplemental data).…”
Section: Discussionmentioning
confidence: 99%
“…The IGLL1 protein has been identified in droppings, bloom, and pigeon serum and PROE protein in droppings and bloom. A strong correlation has been shown between the IgG antibody response of patients sensitized to pigeon, duck and goose antigens 11 . Therefore, we hypothesize that amino-acid sequences close to those found in IGLL1 and PROE are part of proteins from the feathers (goose, duck) used for the manufacture of pillows and duvets.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation